2010
DOI: 10.1088/0022-3727/43/5/055302
|View full text |Cite
|
Sign up to set email alerts
|

Ar plasma treatment on few layer graphene sheets for enhancing their field emission properties

Abstract: Plasma treatment in Ar gas on few layer graphene sheets (FLGSs), synthesized by plasma enhanced chemical vapour deposition, has been performed for enhancing their field emission properties. The plasma etching treatment for 3 min on the FLGSs, forming an extremely sharp edge, decreases the turn-on electric field from 3.91 to 2.23 V µm−1, and increases the maximum emission current density, drawn at a field of 4.4 V µm−1, from 33 to 1330 µA cm−2. It is expected that plasma treatment provides an efficient way to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 19 publications
1
36
1
Order By: Relevance
“…Our previous work demonstrated that PECVD is a simple, low cost, and reliable technique to obtain high-quality graphene, including vertically aligned graphene sheets on Si substrate [35,36]. In this work, vertically aligned graphene nanosheets were synthesized on Ni foam.…”
Section: Synthesis Of Gnsmentioning
confidence: 99%
“…Our previous work demonstrated that PECVD is a simple, low cost, and reliable technique to obtain high-quality graphene, including vertically aligned graphene sheets on Si substrate [35,36]. In this work, vertically aligned graphene nanosheets were synthesized on Ni foam.…”
Section: Synthesis Of Gnsmentioning
confidence: 99%
“…Qi et al synthesized few-layer graphene sheets (FLGSs) by plasma enhanced chemical vapour deposition (PECVD) technique and demonstrated that the field emission properties can be improved by Ar plasma treatment of FLGSs [9]. Malesevic et al have reported a good field emission property of vertically aligned FLGSs synthesized using PECVD technique [10].…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] For example, various plasma treatments have been employed to modify the physical, chemical, and electronic properties of graphene. [26][27][28][29][30][31] For instance, Nourbakhsh 32 and Gokus et al 28 demonstrated bandgap opening of graphene via oxygen plasma treatment. Similar plasma treatments of graphene were reported by Shen et al for the purpose of charge-transport properties control 26 and electrocatalytic activity enhacement.…”
mentioning
confidence: 99%